Near-infrared laser-irradiated upconversion nanoparticles with dexamethasone precise released for alleviating lung ischemia-reperfusion injury - He, Xiaojing; Li, Zhining; Ye, Mengling; Zhao, Chen; Wu, Siyi; Qin, Yi; Guo, Youyuan; Zhang, Lu; Lin, Fei (Frontiers in Bioengineering and Biotechnology, 2023)
Dexamethasone (DEX), as an important enduring-effect glucocorticoid (GC), holds great promise in the field of lung ischemia-reperfusion injury (LIRI) comprehensive therapy owing to its immunomodulatory properties, such as inducing apoptosis and cell cycle distribution. However, its potent auxiliary anticancer and anti-inflammatory application is still restricted because of multiple internal physiologic barriers. Herein, we developed upconversion nanoparticles (UCNPs) coated with photosensitizer/capping agent/fluorescent probe-modified mesoporous silica (UCNPs@mSiO2[DEX]-Py/β-CD/FITC, USDPFs) for precise DEX release synergistic LIRI comprehensive therapy. The UCNPs were designed by covering an inert YOF:Yb shell on the YOF:Yb,Tm core to achieve high-intensity blue and red upconversion emission upon Near-Infrared (NIR) laser irradiation. Under suitable compatibility conditions, the molecular structure of photosensitizer can be damaged along with capping agent shedding, which endowed USDPFs with an outstanding capability to carry out DEX release controlling and fluorescent indicator targeting. Furthermore, the hybrid encapsulating of DEX significantly increased utilization of chemotherapy nano-drugs, improving the water solubility and bioavailability, which was conducive to developing the chemotherapy performance of USDPFs in the complex clinical environment. Furthermore, the response-controlled release of DEX in the intrapulmonary microenvironment can reduce normal cell killing, which can effectively avoid the side effects of nano-drugs in chemotherapy. Meanwhile, the multi-wavelength of UCNPs endowed nano-drugs with the fluorescence emission imaging capacity in an intrapulmonary microenvironment, providing precise guidance for LIRI.